Answer:
![\displaystyle k = \frac{5}{6}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20k%20%3D%20%5Cfrac%7B5%7D%7B6%7D)
Step-by-step explanation:
We are given the equation:
![\displaystyle (2k+1)x^2 + 2x = 10x - 6](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%282k%2B1%29x%5E2%20%2B%202x%20%3D%2010x%20-%206)
And we want to find the value of <em>k</em> such that the equation has two real and equivalent roots.
Since the equation is a quadartic, we can find its discriminant (symbolized by Δ). Recall that:
- If Δ < 0, we have no real roots (two complex roots).
- If Δ > 0, we have two real roots.
- And if Δ = 0, we have one real root, or two equivalent ones.
First, rewrite our equation:
![(2k+1)x^2 -8x + 6 =0](https://tex.z-dn.net/?f=%282k%2B1%29x%5E2%20-8x%20%2B%206%20%3D0)
The discriminant is given by:
![\displaystyle \Delta = b^2 -4ac](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5CDelta%20%3D%20b%5E2%20-4ac)
In this case, <em>b</em> = -8, <em>a</em> = (2<em>k</em> + 1), and <em>c</em> = 6.
Therefore, the discriminant is given by:
![\displaystyle \Delta = (-8)^2 - 4(2k+1)(6)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5CDelta%20%3D%20%28-8%29%5E2%20-%204%282k%2B1%29%286%29)
For it to have two equal roots, the discriminant must be zero. Hence:
![\displaystyle 0 = (-8)^2 - 4(2k+1)(6)](https://tex.z-dn.net/?f=%5Cdisplaystyle%200%20%3D%20%28-8%29%5E2%20-%204%282k%2B1%29%286%29)
Solve for <em>k: </em>
<em />
<em />
<em />
Hence, the value of <em>k</em> is 5/6.